2018
DOI: 10.7554/elife.30015
|View full text |Cite
|
Sign up to set email alerts
|

Cdc48 regulates a deubiquitylase cascade critical for mitochondrial fusion

Abstract: Cdc48/p97, a ubiquitin-selective chaperone, orchestrates the function of E3 ligases and deubiquitylases (DUBs). Here, we identify a new function of Cdc48 in ubiquitin-dependent regulation of mitochondrial dynamics. The DUBs Ubp12 and Ubp2 exert opposing effects on mitochondrial fusion and cleave different ubiquitin chains on the mitofusin Fzo1. We demonstrate that Cdc48 integrates the activities of these two DUBs, which are themselves ubiquitylated. First, Cdc48 promotes proteolysis of Ubp12, stabilizing pro-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 84 publications
0
45
0
Order By: Relevance
“…The DUBs USP15 and USP30 oppose parkin-mediated mitochondrial ubiquitination and mitophagy in cultured human cells. Interestingly, the yeast homologue of USP15 (Ubp12) deubiquitinates the MOM protein Fzo1, the yeast homologue of the mammalian parkin substrates mitofusin 1 and 2, pointing to a conserved role for USP15 in deubiquitination at the MOM ( Anton et al, 2013 ; SimoesSimões et al, 2018 ). Knockdown of the Drosophila homologs of USP15 ( CG8334 , hereafter called dUSP15 ) and USP30 ( CG3016 , hereafter dUSP30 ) largely rescues the mitochondrial defects of parkin-deficient fly muscle in vivo ( Bingol et al, 2014 ; Cornelissen et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The DUBs USP15 and USP30 oppose parkin-mediated mitochondrial ubiquitination and mitophagy in cultured human cells. Interestingly, the yeast homologue of USP15 (Ubp12) deubiquitinates the MOM protein Fzo1, the yeast homologue of the mammalian parkin substrates mitofusin 1 and 2, pointing to a conserved role for USP15 in deubiquitination at the MOM ( Anton et al, 2013 ; SimoesSimões et al, 2018 ). Knockdown of the Drosophila homologs of USP15 ( CG8334 , hereafter called dUSP15 ) and USP30 ( CG3016 , hereafter dUSP30 ) largely rescues the mitochondrial defects of parkin-deficient fly muscle in vivo ( Bingol et al, 2014 ; Cornelissen et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in yeast showed that CDC48 proteins play a role in mitochondria fusion by regulating Fzo1 ubiquitylation and dynamics. Mutations in CDC48 cause mitochondria aggregation and fragmentation (Esaki and Ogura, 2012;Chowdhury et al, 2018;Simões et al, 2018). In addition, CDC48 is also involved in degradation of other mitochondrial outer membrane proteins such as Mdm34, Msp1, Tom70, and oxidation damaged mitochondrial proteins in yeast and Mcl1 in human (Xu et al, 2011;Hemion et al, 2014;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Under non-stressed conditions Fzo1 and additional other OMM proteins are targeted by another Cdc48 complex involving Npl4, Ufd1, and Doa1, also called Ufd3 (Wu et al, 2016) (Figure 1 and Table 1). This might however reflect protein quality control triggered by experimental tagging of the membrane-bound proteins, since non-tagged endogenous Fzo1 is rather stabilized by Cdc48, which exerts a regulatory role during OMM fusion (Simões et al, 2018;Anton et al, 2019). Turnover of mitofusins by MAD is widely conserved among species including Marf in flies (Ziviani et al, 2010;Wang et al, 2016) and Mfn1/2 in mammals (Tanaka et al, 2010;Chan et al, 2011;Xu et al, 2011).…”
Section: Ups-dependent Turnover Of Mitochondrial Proteinsmentioning
confidence: 99%